Unpredictable Solutions of Impulsive Quasi-Linear Systems - Akhmet, Marat; Tleubergenova, Madina; Nugayeva, Zakhira (Discontinuity, Nonlinearity, and Complexity, 2026)
The impulsive differential equations with unpredictable perturbations are under investigation. The definition of the discontinuous unpredictable function with the discrete unpredictable set of discontinuity moments is introduced. The existence and uniqueness of asymptotically stable discontinuous unpredictable solutions for quasi linear systems are proved. Examples with simulations are given to illustrate the results.